Perancangan Dan Analisis Belt Conveyor Kapasitas 150 Ton/Jam Berdasarkan Standar CEMA Dan DIN 22101 - Juliandi Ashari; Musthafa Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The conveyor belt is one of the most widely used material conveyances in industry. In addition to the distance that can be traveled quite far, this tool also has a large enough carrying capacity. In this study, the belt conveyor was designed using two standards, namely CEMA and DIN. From the calculation results, the dimensions of the components and the motor power on the conveyor belt are obtained. The results of the calculation of the standard CEMA belt width 457.2 mm, idler diameter 152.4 mm, motor power 23.86 kW, pulley diameter 355.6 mm and DIN calculation results are belt width 400 mm, idler diameter 102 mm, motor power 22, 36 kW, pulley diameter 355.6 mm. From the calculation results, it is known that all components in the CEMA standard have dimensions and motor power that is greater than the DIN standard, in general this is because the CEMA standard uses more safety factors so that the motor power required in the CEMA standard is greater than the DIN standard. In the calculation results, the maximum yield stress on the pulley is 15.62 MPa and at the idler roller is 0.393 MPa, so based on the yield stress of the material, namely ASTM A36 of 400 Mpa, it can be ascertained that the structure is able to withstand the given load. Meanwhile, the maximum deflection at the pulley is 0.0138 mm and at the idler roller is 0.00019 mm. Keyword : belt conveyor, belt, roller idler, drive motor.